Jellynolide A, pokepola esters, and sponalisolides from the aquaculture sponge Spongia officinalis L. (February 2022) - Jin, Tianyun; Li, Pinglin; Wang, Cili; Tang, Xuli; Yu, Xiaoli; Sun, Fengqing; Luo, Lianzhong; Ou, Huilong; Li, Guoqiang
Abstract: Jellynolide A, an unreported bicyclic diterpenoid with an unprecedented penta-substituted carbon skeleton which implied an irregular biogenic pathway, together with four pairs of rare phosphate triesters, (±)-pokepola ester B−E, one undescribed related racemic furanoterpenoid, (±)-sponalisolide C, one undescribed furanoterpenoid, (−)-sponalisolide D, and two known (±)-sponalisolide B and dendrolasin carboxylic acid were isolated from the aquaculture Spongia officinalis L. Their structures were elucidated by comprehensive spectroscopic analysis, quantum chemical calculation of NMR parameters, and electronic circular dichroism (ECD). The plausible biosynthetic pathway of jellynolide A was proposed. (±)-Pokepola ester C exhibited significant inhibition against Wnt, HIF1 signaling pathways. (+)-Pokepola ester B and (−)-pokepola ester D showed moderate cytotoxicity activities. Graphical abstract: Image 1 Highlights: An unprecedented diterpenoid with an novel carbon skeleton. Four pairs of rare phosphate triesters and two new furanoterpenoids Their structures were elucidated by NMR, DP4+ and ECD. Compounds exhibited significant inhibition against Wnt, HIF1 signaling pathways.